Những vấn đề văn hóa học lý luận và ứng dụng. - Trần Ngọc Thêm (Tủ sách Văn hóa học Sài Gòn, 2014)
Những vấn đề văn hóa học lý luận. Những vấn đề văn hóa Việt Nam. Những vấn đề văn hóa thế giới. Những vấn đề văn hóa học ứng dụng.